THE MIDDLE EOCENE CLIMATIC OPTIMUM (MECO) IMPACT ON THE BENTHIC AND PLANKTIC FORAMINIFERAL RESILIENCE FROM A SHALLOW-WATER SEDIMENTARY RECORD (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
We present here new quantitative analyses of planktic and benthic foraminifera to assess the impact of the Middle Eocene Climatic Optimum (MECO, ~40 Ma) on these biotic groups studied along a shallow-water succession rich in larger benthic foraminifera (Sealza, Liguria, NW Italy). The MECO is one of the major Eocene global warming events, characterized by ~4–6°C warming, shifts in the global carbon cycle, and rise in atmospheric pCO2. The Sealza succession is interpreted as the product of a drowning ramp influenced by tectonic activity and provides an exceptional chance to compare biotic variations in shallow-water assemblages with deep-water communities across the MECO. In the section, the MECO interval is tentatively constrained by stable isotope oxygen data and calcareous plankton biostratigraphy. The marked decline in abundance of the epifaunal benthic Cibicidoides across the lower-middle part of the MECO suggests a decrease in oxygenation at the seafloor. Further evidence of oxygen depletion is the increase in organic matter content (TOC) of the sediment and the presence of infaunal genera Uvigerina and Bolivina. The planktic foraminiferal assemblages record the MECO warming in the upper water column as the mixed-layer warm index genera Acarinina and Morozovelloides markedly increase in abundance. In the post-MECO interval, here poorly exposed, cooler conditions are indicated by the dominance of the cold-water index genus Subbotina. Remarkably, Acarinina decline in abundance in the upper MECO interval and never recover. The MECO perturbance permanently impacted the benthic and planktic communities at Sealza that exceeded the tipping point to move to a new regime, thus proving the fauna to be not resilient, but also not recording any extinctions.
Keywords: Bartonian; biodiversity; biostratigraphy; paleoenvironments; Ligurian Alps.